The prevalence and factors associated with ocular complications among patients with type 2 diabetes in Onandjokwe hospital - Njuki, Peter Ngungi (Stellenbosch : Stellenbosch University, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.